A case of hereditary combined deficiency of complement components C6 and C7 in man. - Morgan, B P (1989)
Immunological investigation of a patient presenting with candidiasis and toxoplasmosis revealed a combined deficiency of C6 and C7. Deficiency of C6 was total, but small amounts (less than 1 microgram/ml) of apparently normal C7 were present in the serum. All family members (three sibs and both parents) were heterozygous for the combined deficiency. This is only the second reported case of combined homozygous deficiency of the closely linked and immunochemically similar proteins C6 and C7, and only the third kindred in which this defect has been demonstrated.